2015
DOI: 10.1002/anie.201503150
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Materials from Nature through Nanotechnology: A Sustainable Route from Reed Plants to a Silicon Anode for Lithium‐Ion Batteries

Abstract: Silicon is an attractive anode material in energy storage devices, as it has a ten times higher theoretical capacity than its state-of-art carbonaceous counterpart. However, the common process to synthesize silicon nanostructured electrodes is complex, costly, and energy-intensive. Three-dimensional (3D) porous silicon-based anode materials have been fabricated from natural reed leaves by calcination and magnesiothermic reduction. This sustainable and highly abundant silica source allows for facile production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(134 citation statements)
references
References 50 publications
0
134
0
Order By: Relevance
“…This is because of their unique architecture: 1) the introduction of the interconnected carbon network inside the silicon granadillas and the unique double-carbon-shell structure can effectively strengthen the mechanical properties, improve the electrical conductivity, and prevent the electrolyte ingress; [ 37,[43][44][45][46] 2) the developed porous carbon supported yolkshell structure can provide additional storage sites for lithium ions, [ 47 ] better absorb the huge volume change of silicon during cycling, and prevent the aggregation of Si NPs; [ 25,48,49 ] 3) the homogenous microspherical morphology leads to less tortuosity of electrode and higher electrolyte diffusion, thus enhancing the rate performance. [50][51][52][53][54][55][56] …”
Section: Resultsmentioning
confidence: 99%
“…This is because of their unique architecture: 1) the introduction of the interconnected carbon network inside the silicon granadillas and the unique double-carbon-shell structure can effectively strengthen the mechanical properties, improve the electrical conductivity, and prevent the electrolyte ingress; [ 37,[43][44][45][46] 2) the developed porous carbon supported yolkshell structure can provide additional storage sites for lithium ions, [ 47 ] better absorb the huge volume change of silicon during cycling, and prevent the aggregation of Si NPs; [ 25,48,49 ] 3) the homogenous microspherical morphology leads to less tortuosity of electrode and higher electrolyte diffusion, thus enhancing the rate performance. [50][51][52][53][54][55][56] …”
Section: Resultsmentioning
confidence: 99%
“…However, the huge volume changes during lithiation and de-lithiation process always leads to poor cycle performance and electrical contact, which severely hinders the industrial applications of silicon-based anode materials (Candace et al, 2009;Hertzberg et al, 2010;Bo et al, 2016;Li et al, 2016Li et al, , 2017. Currently, some approaches have been designed to accommodate the volume change by introducing void spaces or improving the linkage between Si particles, and further enhance the cycling performance of Si materials, such as decreasing Si into nanoscale size (Chen et al, 2010;Szczech and Jin, 2010;Hu et al, 2011;Liu et al, 2011Liu et al, , 2015) (e.g., silicon nanowires, silicon nanotubes, and silicon nanoarrays); developing Si into thin-film electrodes (Arie et al, 2009;Tao et al, 2011); optimizing the morphology of silicon to improve the electronic contact of silicon with current collector (Zheng et al, 2007;Peng et al, 2010) or dispersing silicon into a dimensional stable matrix (Ng et al, 2006;Zhang et al, 2010;Yi et al, 2013). On the other hand, SiOx nanocomposites also have attracted considerable attention because the in situ generated Li2O during the first discharge process can buffer the volume changes during lithiation/ delithiation process and further improve the cycling performance of electrode (Hu et al, 2008).…”
mentioning
confidence: 99%
“…67,68 For example, Yu et al used reed leaves as the silica precursor to prepare the porous silica, and three-dimensional (3D) interconnected porous silicon was then synthesized via a magnesiothermic method (Figure 3c and 3d). 60 Nitrogen adsorption (Brunauer-Emmett-Teller, BET) measurements indicated that the initial 3D mesoporous silica precursor had a BET surface area of 101 m 2 g -1 and a total pore volume of 0.22 cm 3 g -1 . More importantly, even after the magnesiothermic reduction and the final carbon coating process, the prepared silicon anode still retained the original skeleton morphology of the reed leaves, which means good structural and thermal stability for this material.…”
Section: Natural Plantsmentioning
confidence: 99%
“…Secondly, a highly interconnected porous structure is created due to the etching of the MgO inclusions inside the sample during the magnesiothermic reduction. 60 Thirdly, the low processing temperature and short reaction time make this method more attractive than alternative methods. 61…”
Section: Silicamentioning
confidence: 99%
See 1 more Smart Citation